Tijārah in Colonial and Contemporary Qur’anic Translations: Meaning Transformation and Implications for Islamic Economic Law Understanding - Muhamad Saiful Mukminin; Muhammad Habibie Alfath (UIN Mahmud Yunus Batusangkar, 2026)
Differences and changes in meaning in the translation of Qur’anic terms have the potential to influence the understanding of religious concepts, particularly in the field of Islamic economic law. Using a qualitative approach, this study explores the transformation of the meaning of tijārah in Qur’anic translations across two versions, namely the colonial and contemporary translations, and analyzes the factors causing this transformation as well as its implications for the understanding and construction of Islamic economic law. The data of this study consist of the word tijārah in the Qur’an along with its two translation versions, namely the colonial translation by Mahmud Yunus and the contemporary translation by the Ministry of Religious Affairs of the Republic of Indonesia. The data collection technique employs observation and note-taking methods, while data analysis is conducted through data reduction, data display, and conclusion drawing. The findings reveal three patterns of transformation, namely stability, de-explicitation, and lexical shift. These transformations are influenced by translation ideology, language development, socio-historical context, and the epistemology of Islamic law. This study concludes that translation is ideological in nature and has implications for the understanding of contracts (ʿaqd), the concept of profit, legal flexibility, and the space for contemporary ijtihād in Islamic economic law.